The Holistic Effects of Mystical Union with Christ in the Soteriology of Dhanjibhai Fakirbhai - Burbank, Ray (Mission studies, 2024)
This article addresses the relationship between eschatological and present issues in Christian soteriological debates of the mid-twentieth century, particularly in post- colonial India. It focuses on the writings of Dhanjibhai Fakirbhai. As mystical views of Christian salvation can be criticized for their irrelevancy to secular society, Dhanjibhai presents a contrast to this in a type of mystical soteriology that breaks such critiques and complicates the usual categories of South Asian understandings. According to Dhanjibhai, “salvation” means to be in union with Jesus Christ, a spiritual faith-based relationship that extends into eternity but is also practically experienced in the world today. This article proceeds according to four key features of Dhanjibhai’s writings that demonstrate the holistic effects of union with Christ in his soteriology. I argue that Dhanjibhai alleviates the perceived problems of mystical approaches by presenting a soteriology that envelopes personal, social, and even ecological ramifications of salvation within a contextual evangelical framework.